The Influence of Diabetes, Glycemic Control, and Diabetes-Related Comorbidities on Pulmonary Tuberculosis - Chiang, Chen Yuan; Bai, Kuan Jen; Lin, Hsien Ho; Chien, Shun Tien; Lee, Jen Jyh; Enarson, Donald A.; Lee, Ting-I; Yu, Ming-Chih (PLOS ONE, 2015)
To assess the influence of diabetes mellitus (DM), glycemic control, and diabetes-related comorbidities on manifestations and outcome of treatment of pulmonary tuberculosis (TB). Culture positive pulmonary TB patients notified to health authorities in three hospitals in Taiwan from 2005-2010 were investigated. Glycemic control was assessed by glycated haemoglobin A1C (HbA1C) and diabetic patients were categorized into 3 groups: HbA1C<7%, HbA1C 7-9%, HbA1C>9%. 1,473 (705 with DM and 768 without DM) patients were enrolled. Of the 705 diabetic patients, 82 (11.6%) had pretreatment HbA1C<7%, 152 (21.6%) 7%-9%, 276 (39.2%) >9%, and 195 (27.7%) had no information of HbA1C. The proportions of patients with any symptom, cough, hemoptysis, tiredness and weight loss were all highest in diabetic patients with HbA1C>9%. In multivariate analysis adjusted for age, sex, smoking, and drug resistance, diabetic patients with HbA1C>9% (adjOR 3.55, 95% CI 2.40-5.25) and HbA1C 7-9% (adjOR 1.62, 95% CI 1.07-2.44) were significantly more likely to be smear positive as compared with non-diabetic patients, but not those with HbA1C<7% (adjOR 1.16, 95% CI 0.70-1.92). The influence of DM on outcome of TB treatment was not proportionately related to HbA1C, but mainly mediated through diabetes-related comorbidities. Patients with diabetes-related comorbidities had an increased risk of unfavorable outcome (adjOR 3.38, 95% CI 2.19-5.22, p<0.001) and one year mortality (adjOR 2.80, 95% CI 1.89-4.16). However, diabetes was not associated with amplification of resistance to isoniazid (p = 0.363) or to rifampicin (p = 0.344). Poor glycemic control is associated with poor TB treatment outcome and improved glycemic control may reduce the influence of diabetes on TB.